Infection with Mycobacterium avium subsp. paratuberculosis Results in Rapid Interleukin-1β Release and Macrophage Transepithelial Migration - Lamont, Elise A. (American Society for Microbiology, 2012)
Pathogen processing by the intestinal epithelium involves a dynamic innate immune response initiated by pathogen-epithelial cell cross talk. Interactions between epithelium and Mycobacterium avium subsp. paratuberculosis have not been intensively studied, and it is currently unknown how the bacterium-epithelial cell cross talk contributes to the course of infection. We hypothesized that M. avium subsp. paratuberculosis harnesses host responses to recruit macrophages to the site of infection to ensure its survival and dissemination. We investigated macrophage recruitment in response to M. avium subsp. paratuberculosis using a MAC-T bovine macrophage coculture system. We show that M. avium subsp. paratuberculosis infection led to phagosome acidification within bovine epithelial (MAC-T) cells as early as 10 min, which resulted in upregulation of interleukin-1β (IL-1β) at transcript and protein levels. Within 10 min of infection, macrophages were recruited to the apical side of MAC-T cells. Inhibition of phagosome acidification or IL-1β abrogated this response, while MCP-1/CCL-2 blocking had no effect. IL-1β processing was dependent upon Ca(2+) uptake from the extracellular medium and intracellular Ca(2+) oscillations, as determined by EGTA and BAPTA-AM [1,2-bis(2-aminophenoxy) ethane-N,N,N′,N′-tetraacetic acid tetrakis (acetoxymethyl ester)] treatments. Thus, M. avium subsp. paratuberculosis is an opportunist that takes advantage of extracellular Ca(2+)-dependent phagosome acidification and IL-1β processing in order to efficiently transverse the epithelium and enter its niche—the macrophage.